Tight junction composition is altered in the epithelium of polycystic kidneys - Yu, ASL; Kanzawa, SA; Usorov, A; Lantinga-van Leeuwen, IS; Peters, DJM (The Journal of pathology, 2008)
Kidney cysts in autosomal dominant polycystic kidney disease (ADPKD) undergo progressive enlargement together with luminal fluid secretion. This involves active, uphill transcellular Cl⁻ transport which drives passive Na⁺ and water secretion. Implicit in this mechanism is the assumption that the paracellular permeability of the cyst epithelium to Cl⁻ must be very low. Claudins are tight junction (TJ) transmembrane proteins that determine the ion selectivity of paracellular barriers. The aim of this study was to determine the expression and localization of claudins within renal cysts in a mouse hypomorphic model of ADPKD and in human patients. We found that the majority of cysts were of collecting duct origin. Claudins normally expressed in collecting duct (3, 4, 7, 8, and 10) were found in small cysts. However, only claudin-7 persisted at substantive levels in the dedifferentiated epithelium of large, presumably late-stage cysts, where it was localized both at the TJ and basolaterally. The constitutively expressed TJ proteins, ZO-1 and occludin, were also abundantly expressed and correctly localized, suggesting that the basic infrastructure of the TJ is preserved. A previous study suggested that claudin-7 may function as a paracellular Cl⁻ barrier. We postulate that the role of claudin-7 in ADPKD is to seal the paracellular route in Cl⁻-secreting cyst epithelium, preventing backleak of Cl⁻, and that it thereby plays a permissive role in fluid secretion and cyst growth. Copyright © 2008 Pathological Society of Great Britain and Ireland. Published by John Wiley & Sons, Ltd.